2004
DOI: 10.1111/j.1527-3458.2004.tb00025.x
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Pharmacology of NCS‐382, a Putative Antagonist of γ‐Hydroxybutyric Acid (GHB) Receptor

Abstract: Gamma-hydroxybutyric acid (GHB), a naturally occurring metabolite of gamma-aminobutyric acid (GABA), has been postulated to act as a specific agonist of GHB receptors and as well as a weak GABA(B) receptor agonist. To date, 6,7,8,9-tetrahydro-5-hydroxy-5H-benzocyclohept-6-ylideneacetic acid (NCS-382), a semirigid compound structurally related to GHB, is the only compound reported to be an antagonist of the GHB receptor sites. In this article we review the in vivo and in vitro pharmacological properties of NCS-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
36
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 67 publications
1
36
0
Order By: Relevance
“…Taken together, these results suggest that the specific-GHB binding site contributes minimally to the above effects of GHB and its precursors. Alternatively, it can be hypothesized that NCS-382 may not be particularly selective for the specific-GHB binding site (15) or even possess agonistic properties at this binding site (28), leaving the contribution of this binding site on GHB, 1,4-BD, and GBL pharmacology an open issue. Accordingly, it is worthy of note that the recently cloned specific-GHB binding site was insensitive to NCS-382, suggesting the possible existence of different subtypes of this binding site (29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taken together, these results suggest that the specific-GHB binding site contributes minimally to the above effects of GHB and its precursors. Alternatively, it can be hypothesized that NCS-382 may not be particularly selective for the specific-GHB binding site (15) or even possess agonistic properties at this binding site (28), leaving the contribution of this binding site on GHB, 1,4-BD, and GBL pharmacology an open issue. Accordingly, it is worthy of note that the recently cloned specific-GHB binding site was insensitive to NCS-382, suggesting the possible existence of different subtypes of this binding site (29).…”
Section: Discussionmentioning
confidence: 99%
“…Different lines of experimental evidence suggest the existence of a second GHB site of action, represented by a specific-GHB binding site (1,14). In order to evaluate the possible contribution of this substrate to the above GBL effects, the present study also included a series of experiments with NCS-382, a putative antagonist of the specific-GHB binding site (15).…”
mentioning
confidence: 99%
“…This appears unlikely, however, because in vivo studies with NCS-382 suggest that it interacts with a functional receptor; that is, NCS-382 administration diminishes the sedative and cataleptic effects of GHB and blocks the enhancing effects on the spontaneous firing rate of cortical neurons at low doses of GHB but not the depressant effects seen at higher doses (14,15). Because NCS-382 administration blocks neither GHB-induced ataxia nor its depressant effects on locomotor activity, learned and unlearned behavior, and operant responses (16,17), these actions are probably mediated by GHB activation of GABA B receptors.…”
mentioning
confidence: 99%
“…In further support of this view, brains from GABA B(1) receptor knock-out mice still exhibit [ 3 H]GHB binding (Kaupmann et al, 2003;Wu et al, 2004), demon-strating that GHB and GABA binding sites are separate entities. NCS-382, a synthetic structural analog of GHB and a purported antagonist of the GHB receptor (Castelli et al, 2004), has been shown to compete with [ 3 H]GHB for the high-affinity sites. Radioligand binding studies have demonstrated [ 3 H]NCS-382 to be selective for GHB binding sites, making it a valuable tool for probing the putative GHB receptor (Mehta et al, 2001).…”
mentioning
confidence: 99%